The Combination of Mesenchymal Stem Cells and Bovine Colostrum in Reducing α-SMA Expression and NLR Levels in Wistar Rats After 50% Fibrotic Liver Resection - Hartanto, Michael Mawi; Prajoko, Yan Wisnu; Putra, Agung; Amalina, Nur Dina (Open Access Macedonian Journal of Medical Sciences, 2022)
Background: Liver fibrogenesis will produce α-smooth muscle actin (α-SMA) expression and a continuous inflammatory process, seen through the neutrophil lymphocyte ratio (NLR). The combination of mesenchymal stem cells and bovine colostrum is a novel strategy for repairing hepatic fibrosis tissue. To assess the combination of mesenchymal stem cells and bovine colostrum to reduce α-SMA expression and NLR levels in Wistar rats after 50% fibrotic liver resection. Methods: Thirty-six Wistar male rats were randomly divided into 6 groups (sham, control, colostrum, MSCs, and colostrum and MSCs combination). Rats were injected with CCl4 for 8 weeks to induce liver fibrosis then underwent liver resection. NLR levels was determined using Hematology Analyzer, α-SMA expression of myofibroblast was analyzed by immunofluorescence staining. Results: A significant reduction in NLR levels on day 3 in the treatment group I (1.10), treatment II (0.83), treatment III (0.93) compared to the control group. A significant reduction in NLR levels on day 10 in the treatment group I (0.76), treatment II (0.64), treatment III (0.54) compared to the control group. A significant decrease in α-SMA in treatment group I (0.134), treatment II (0.68), treatment III (0.42) compared to the control group. Conclusion: In this study, it was found that α-SMA expression, NLR levels on the 3rd and 10th day of administration were reduced in group receiving combination of mesenchymal stem cells and bovine colostrum in the liver of post-resection Wistar rats by 50%.